2021
DOI: 10.3390/ijms221910763
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of Intestinal Organoid from Rousettus leschenaultii and the Susceptibility to Bat-Associated Viruses, SARS-CoV-2 and Pteropine Orthoreovirus

Abstract: Various pathogens, such as Ebola virus, Marburg virus, Nipah virus, Hendra virus, Severe Acute Respiratory Syndrome Coronavirus (SARS-CoV), Middle East Respiratory Syndrome Coronavirus (MERS-CoV), and SARS-CoV-2, are threatening human health worldwide. The natural hosts of these pathogens are thought to be bats. The rousette bat, a megabat, is thought to be a natural reservoir of filoviruses, including Ebola and Marburg viruses. Additionally, the rousette bat showed a transient infection in the experimental in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 58 publications
2
12
0
Order By: Relevance
“…Organoids from Chinese horseshoe bats, where SARS-CoV-2-like virus has been detected 7 , produced infectious SARS-CoV-2 virions at similar levels as human intestinal organoids 25 . In contrast, intestinal organoids from Leschenault's rousette bats (Rousettus leschenaultii) failed to support SARS-CoV-2 replication 23 . Interestingly, PCR analysis revealed a signi cant increase in viral and sgRNA in the JFB distal organoids at 48 and 72 hpi, which demonstrates initiation of viral replication in the organoids.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Organoids from Chinese horseshoe bats, where SARS-CoV-2-like virus has been detected 7 , produced infectious SARS-CoV-2 virions at similar levels as human intestinal organoids 25 . In contrast, intestinal organoids from Leschenault's rousette bats (Rousettus leschenaultii) failed to support SARS-CoV-2 replication 23 . Interestingly, PCR analysis revealed a signi cant increase in viral and sgRNA in the JFB distal organoids at 48 and 72 hpi, which demonstrates initiation of viral replication in the organoids.…”
Section: Discussionmentioning
confidence: 94%
“…Importantly, growth conditions for GI organoids appear similar across multiple species 22 . Two previous studies have described the generation of intestinal organoid cultures from bat species 23,24 . Intestinal organoids developed from Chinese horseshoe bats, Rhinolophus sinicus, showed susceptibility to SARS-CoV-2, but lacked long-term active proliferation past 4-5 weeks 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies reported the generation of intestinal organoids from Chinese horseshoe bat, Rhinolophus sinicus [ 14 ] and Leschenault's rousette, Rousettus leschenaultia [ 15 ]. To our knowledge, this is the first study to establish a sustainable approach for the propagation of bat airway organoids, and their conversion into ALI-AECs to aid infection studies.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with these environmental sampling data. Similarly, it was observed that intestinal organoids from another Pteropodid bat, R. leschenaultia , were not susceptible to SARS-CoV-2 [ 15 ], while intestinal organoids from a Rhinolophus species readily supported SARS-CoV-2 replication [ 28 ]. The observed lack of susceptibility to SARS-CoV-2 is despite the E. spelaea ACE2 receptor homologue mediating SARS-CoV-2 spike pseudovirus entry.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, they provide structural stability vital for cell self-assembly [ 459 ]. Such systems fit a broad spectrum of applications in the biomedical scope, mainly in elevated-throughput drug inspection [ 460 , 461 ], cell biology [ 15 ], cancer biology [ [462] , [463] , [464] , [465] , [466] , [467] , [468] ], disease modeling [ 469 , 470 ], and tissue engineering [ 459 ]. Collectively, hydrogel matrices not only present encouraging results for 3D cell culture but also exhibit high promising potentials for future broad range applications in the biomedical fields, chiefly tissue engineering [ 471 ].…”
Section: Smart/stimuli-responsive Hydrogels For 3d Cell Culturementioning
confidence: 99%